The impact of surgical treatment of benign ovarian tumors on the reproductive health of women, taking into account the International Classification of Functioning - I. S. Zakharov; D. V. Kovlen; A. A. Bezmenko; E. F. Kondrina; A. A. Nazarenko; N. А. Trigubchuk; G. G. Shaginyan (Опухоли женской репродуктивной системы, 2024)
The article presents a systematic analysis of studies evaluating the impact of surgical treatment of benign ovarian tumors on reproductive health, taking into account the criteria stated by the International Classification of Functioning, Disability and Health. To identify articles, foreign and domestic scientific databases were used (PubMed, Cochrane, eLibrary). After the initial identification of 704 scientific publications, 46 articles were selected using inclusion and exclusion criteria.The conducted systemic analysis allows us to formulate the conclusion that surgical interventions performed for benign ovarian tumors contribute to damage to ovarian tissue, and as a result, a decrease in the ovarian reserve of patients, which is associated with impaired fertility. A number of authors have demonstrated some recovery of anti-Mullerian hormone (AMH) levels 3-12 months after surgery. A significant portion of the studies have demonstrated a more pronounced postoperative decrease in AMH rates in patients with endometriomas compared with women operated on for non-endometrioid ovarian tumors. Lower AMH rates were noted in women with bilateral surgeries for bilateral ovarian tumors compared to patients who had unilateral surgeries. The performed systemic analysis showed higher postoperative AMH rates in patients with intraoperative suture hemostasis in comparison with the use of bipolar energy; in addition, there is a relationship between the number of coagulations and the severity of the decrease in AMH rates. In a few studies, it was noted that patients who underwent surgical treatment of ovarian tumors experienced an earlier onset of menopause. In connection with these possible functional disorders, further clinical studies of a high level of evidence are needed, aimed at developing effective strategies for preserving the functioning of the reproductive system after surgical treatment of benign ovarian tumors.